Ecological terms in “baburnama” - Z.Djurabaeva (Indonesian Journal of Innovation Studies, 2019)
The article is devoted to determine the tasks of ecolinguistics as a new branch of linguistics on the one hand, to throw light to the historical-etymological, lexical-semantic peculiarities of the lexical units used in “Baburnama” from the point of drew of ecology, as they make up a separate, system, consisting of definite subsystems.